2011
DOI: 10.1007/s11423-011-9192-7
|View full text |Cite
|
Sign up to set email alerts
|

A study of learning and motivation in a new media enriched environment for middle school science

Abstract: This study examines middle school students' learning and motivation as they engaged in a new media enriched problem-based learning (PBL) environment for middle school science. Using a mixed-method design with both quantitative and qualitative data, we investigated the effect of a new media environment on sixth graders' science learning, their motivation, and the relationship between students' motivation and their science learning. The analysis of the results showed that: Students significantly increased their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
112
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(130 citation statements)
references
References 35 publications
(39 reference statements)
14
112
0
4
Order By: Relevance
“…Based on the questionnaire results, participants demonstrated high levels of communication and interaction and found class activities useful and valuable. Furthermore, our results lend support to previous studies indicating that engagement and motivation are highly rated in technology enhance PBL environments or curriculums, especially when including multimedia [16]. Students' exhibit enthusiasm and positive attitude towards the course and group activities as identified within the qualitative feedback.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Based on the questionnaire results, participants demonstrated high levels of communication and interaction and found class activities useful and valuable. Furthermore, our results lend support to previous studies indicating that engagement and motivation are highly rated in technology enhance PBL environments or curriculums, especially when including multimedia [16]. Students' exhibit enthusiasm and positive attitude towards the course and group activities as identified within the qualitative feedback.…”
Section: Discussionsupporting
confidence: 87%
“…The second main pathway in the use of technology in PBL is multimedia. Researchers created multimedia enriched environments successfully increasing students' motivation [15] [16]. Due to their popularity [17], games were also embraced by PBL community, with efforts made to understand game elements that can lead to the improvement of educational technologies, enhancing students' engagement [18].…”
Section: Use Of Technology In Pblmentioning
confidence: 99%
“…Although verifying such perceptions is not the focus of this study, the clear indication of students' enjoyment of the program and motivation to use it is an important step to help students learn. This finding is consistent with other studies that examined the effects of the PBL program on students' learning and motivation, showing significant gains in science knowledge (Liu, Hsieh, Cho, & Schallert, 2006;Liu et al, 2009;Liu, Horton, Olmanson, & Toprac, 2011).…”
Section: Classroom Goals As Written On the Boardsupporting
confidence: 91%
“…the perceived experience that a learner's behaviour is self-determined, autonomous, or intrinsically motivated) has a strong impact on learning outcomes Liu, Horton, Olmanson, & Toprac, 2011;Martens, Gulikers, & Bastiaens, 2004;Rienties, Tempelaar, Van den Bossche, Gijselaers, motivation, that is a drive to learn based on the satisfaction and pleasure of the activity of learning itself rather than external rewards, significantly predicted science knowledge post-test scores in a blended science game. found that perceived autonomy of 262 learners was the most significant factor predicting learning outcomes in two distance education programmes.…”
mentioning
confidence: 99%